THE SOCIAL ROLE OF INTEGRITY AND ETHICAL VALUES IN THE DEVELOPMENT OF ENTREPRENEURIAL ACTIVITY IN NEW UZBEKISTAN (Scientific journal of the Fergana State University, 2026)
The importance of integrity and ethical values in the development of entrepreneurial activity in the context of New Uzbekistan has been analyzed. Specifically, the social importance of these principles in strengthening trust and justice in society has been highlighted. Additionally, the significance of state policy and legislation in supporting entrepreneurship has been emphasized.